Explaining higher VET dropout rates among adolescents with a migration background in Germany: the role of career compromises - Robin Busse; David Glauser; Katja Scharenberg (Empirical Research in Vocational Education and Training)
Abstract Research has consistently revealed that adolescents with a migration background are more likely to drop out from vocational education and training (VET) at the upper-secondary level than their native peers. While recent research has provided rich empirical evidence of mechanisms leading to dropouts from VET, little is known about such mechanisms for adolescents with a migration background. In our contribution, we assume that the difficulties that adolescents with a migration background face when entering the VET system are associated with a restricted range of occupational opportunities and, thereby, higher levels of career compromises in terms of the desired and attained VET occupation. Following previous findings on key dimensions of career compromise, we examine the relevance of compromises in the field of work and social status in explaining the higher propensity of adolescents with a migration background to drop out from their first VET position. Using logistic regressions and KHB decomposition analyses, our results underline that gaps in VET dropout rates between adolescents with and without a migration background can partially be ascribed to migration-specific compromises in the field of work between the aspired and attained VET occupation, while compromises in social status seem to be unimportant.